The scandal policy and the political scandals in Japan - Alfredo Román Zavala (Portes: Revista mexicana de estudios sobre la Cuenca del Pacífico, 2007)
<p style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; text-align: justify;">This article points out that until a few years ago the power of the Japanese economy, the political stability, the strength of the Japanese bureaucracy, the dominion of a single political party and the negotiation between the private interests and the politicians hid much of the policy making process and darkened the distinction between the public and the private. <p style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; text-align: justify;">Nowadays, with new realities tied to the opening and internationalization of the economy, patterns have arisen from the relation between the economic and political actors in where the sharing of interests is no longer a consensus product. On the contrary, the Japanese policy has dramatic samples of deep polarization and has witnessed the arrival of complexities concerning political negotiation that take political scandal as a form to displace rivals and to complete the decision making process with new players. <p style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; text-align: justify;">Political scandals have "simplified" the political system through mass media. The exhibition of improper acts made by political rivals before the public opinion and the resulting disrepute has modified the relationship between political actors. In such a scenario, the scandals have become a resource and a pernicious strategy that threatens to weaken the bases and stability of the Japanese political system.